I go to the rock : the gospel music of Whitney Houston [compact disc] - Houston, Whitney (Gaither Music Group, 2023)
The unmistakable voice of Whitney Houston is powerful and timeless. She reached the pinnacle of pop success, becoming one of the most accomplished recording artists of all time. But her heart was always in gospel music, and it profoundly influenced her life and career. The 14-track album captures her gospel music journey, featuring 6 never-before-released songs. The recording gives a glimpse of the deep faith behind the voice that continues to uplift and impact countless lives around the world.